2020
DOI: 10.1177/0972652720927856
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Macro-financial Linkages for the Indian Economy

Abstract: The widespread impacts of global financial crisis (2008-09) reinstate the need for better assessment of the macro-financial linkages for forecasting and policy evaluation. Our paper contributes to the relevant literature with evidence from the Indian financial sector. Following Castelnuovo (2013), a New Keynesian model with macro-financial linkages is estimated by the Bayesian technique for the sample period 2004: Q3 to 2019: Q1. We find that, in an Emerging Market Economy like India, business cycle leads fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…She attributed this finding to the choice of reference variable and the use of the multitaper method of the spectrum. A recent study in the Indian context finds that business cycle leading financial cycle through the expectations channel (Banerjee et al, 2021). To be best of our knowledge, there is no study found in the Indian context that examines the properties of financial cycles per se .…”
Section: Literature Reviewmentioning
confidence: 99%
“…She attributed this finding to the choice of reference variable and the use of the multitaper method of the spectrum. A recent study in the Indian context finds that business cycle leading financial cycle through the expectations channel (Banerjee et al, 2021). To be best of our knowledge, there is no study found in the Indian context that examines the properties of financial cycles per se .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the previous works that concentrate on fiscal policy and financial development without addressing this gap (Alenoghena, 2015;Evans, 2020;Gnimassoun & Do Santos, 2021;Ismihan & Ozkan, 2012;Mun & Ismail, 2015;Nwaogwugwu, 2018;Umaru et al, 2023). Also, Banerjee et al (2021) reasoned that the financial sector is strongly linked to macroeconomic performance. Therefore, this research aims to establish the threshold effect of government expenditure on financial depth and examine how the threshold affects the direction of fiscal deficit and domestic debt.…”
Section: Introductionmentioning
confidence: 99%